Figurative Analysis in Wotik Wawi Waten Ceremony - *Elisabeth Jevani Alanti; Antonius M. K. Naro; Yanto Yanto (Universitas Syiah Kuala, 2022)
Figurative language is an interesting phenomenon to be studied and analyzed because it is one of the most arduous topics that literal language processing has to face and it is used in any form of communication. The aims of this study were to identify and analyze figurative language of wotikwawiwaten ceremony. This research used descriptive qualitative research. The techniques of data collection used in this research were interview and study document. The result of this study shows that there are four types of figurative language found; they are simile, repetition, hyperbole, and symbol.